The Indicators of Tolerance Analysis and Tolerance Test of Rice Varieties to NaCl Stress - Novisrayani Kesmayanti; Edy Romza (Faculty of Agriculture, Pattimura University, 2022)
NaCl stress is one of the causes of inhibition and decreased growth of rice plants. The aim of the study was to obtain indicators of tolerance analysis and to analyze the tolerance of rice varieties Inpari-22 and mekongga to NaCl stress. The research was carried out at the Laboratory of Botany and Plant Physiology, Faculty of Agriculture, University of IBA in Palembang, in October-December 2021.The study used a completely randomized factorial design (RALF) 5 x 2. The first factor was the concentration of NaCl, which consisted of 0ppm (water), 2.500ppm, 5.000ppm, 7.500ppm and 10.000ppm. The second factor is rice varieties, namely Inpari-22 and Mekongga. The experiment consisted of 10 treatment combinations with 3 replications. Each experimental unit consisted of 50 seeds, so a total of 1,500 seeds. The results showed that soaking the seeds in a NaCl solution of 2,500-10,000 ppm for 48 hours could increase germination, vigor index, growth speed, growth synchronously and maximum growth potential. However, in subsequent growth there was inhibition and a decrease in plant height, root length, epicotyl length, plant weight and root weight at increasing NaCl concentration from 2,500 ppm -10,000 ppm. In this study, as an indicator of the analysis of seed tolerance to salinity stress, the observations of germination variables (germination, vigor index, growth speed, growth synchronously and maximum growth potential) and early growth half (plant height, number of leaves, root length, epicotyl length, plant weight and root weight) can be used.